Chronic constipation in adults: Contemporary perspectives and clinical challenges. 1: Epidemiology, diagnosis, clinical associations, pathophysiology and investigation. Issue 6 (2nd December 2020) - Scott, S. Mark; Simrén, Magnus; Farmer, Adam D.; Dinning, Philip G.; Carrington, Emma V.; Benninga, Marc A.; Burgell, Rebecca E.; Dimidi, Eirini; Fikree, Asma; Ford, Alexander C.; Fox, Mark; Hoad, Caroline L.; et al.
ABSTRACT: BACKGROUND: Chronic constipation is a prevalent disorder that affects patients' quality of life and consumes resources in healthcare systems worldwide. In clinical practice, it is still considered a challenge as clinicians frequently are unsure as to which treatments to use and when. Over a decade ago, a Neurogastroenterology & Motility journal supplement devoted to the investigation and management of constipation was published (2009; 21 (Suppl.2)). This included seven articles, disseminating all themes covered during a preceding 2‐day meeting held in London, entitled "Current perspectives in chronic constipation: a scientific and clinical symposium." In October 2018, the 3rd London Masterclass, entitled "Contemporary management of constipation" was held, again over 2 days. All faculty members were invited to author two new review articles, which represent a collective synthesis of talks presented and discussions held during this meeting. PURPOSE: This article represents the first of these reviews, addressing epidemiology, diagnosis, clinical associations, pathophysiology, and investigation. Clearly, not all aspects of the condition can be covered in adequate detail; hence, there is a focus on particular "hot topics" and themes that are of contemporary interest. The second review addresses management of chronic constipation, covering behavioral, conservative, medical, and surgical therapies.